(untitled) - Waterhouse, D. F. (Canberra, Autralia, 1989)
The six pest dossiers in this publication follow closely the format adopted in biological control: Pacific prospect. Each was chosen recommendations of the plant protection meetings in Apia in 1986 and Noumea in1987. One of the pest, the Western flower thrips frankliniella occidentalis is not established in the oceanic south west pacific
Keywords: Weeds,Pests,Kiểm soát sinh vật gây hại; Biological control,Biological control; Pacific Area.,Pacific Area